Analysis Of Perceptions Of Ptsl Benefits From Economic, Social/Legal, And Environmental Aspects In Seluma Regency - Arsyah Bentri Putra; Mochamad Ridwan; Izharudin Izharudin; M Armelly; Eka Dewi Anggraini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the perceived benefits of PTSL in Seluma Regency, Bengkulu Province. Seluma Regency is the largest in Bengkulu Province but also has the smallest number of registered and mapped land parcels. This research uses a descriptive research approach. The Analitycal Hierarchy Process (AHP) method was used to determining the priority benefits of PTSL. The results of this study show that the benefits of economic aspects are ranked first with a weight of (0.596) with a sequence of sub-criteria namely Access to Capital / Banking Credit (0.546), Increased Land Value (0.250), Investment in Land (0.120), and Increased BPHTB Revenue (0.120). The benefits of social/legal aspects are ranked second with a weight of (0.287) with a sequence of sub-criteria namely Preventing Conflict Disputes over Land (0.626) and Legal Protection of Land Rights (0.374) and finally the benefits of environmental aspects with a weight of (0.117) with a sequence of sub-criteria of Food Land Function Change (0.761) and Deforestation (0.239).